Peningkatan kinerja guru dalam pembelajaran melalui supervisi edukatif kolaboratif secara periodik di sekolah dasar - Nuryanah, Nuryanah (Universitas Sebelas Maret, 2021)
School Action Research (PTS) was conducted at SDN Kawengen 01, East Ungaran District, Semarang Regency. The subjects in this PTS were teachers of SDN Kawengen 01, East Ungaran Subdistrict, Semarang Regency, totaling 9 teachers consisting of 6 class teachers and 3 subject teachers.The results of this study are that collaborative educational supervision can improve teacher performance in planning lessons at SDN Kawengen 01, East Ungaran District, Semarang Regency, 2019/2020 Academic Year. In terms of quality, the teacher's performance in planning learning was 49.1%, there was an increase of 17.9% so that it increased to 67.0% in cycle I, and an increase of 18.2% so that it increased to 85.2% in cycle II. In terms of quantity, the teacher's performance in planning learning was 33%, there was an increase of 45% so that it increased to 78% in cycle I, and an increase of 22% so that it increased to 100.0% in cycle II. So it can be concluded that collaborative educational supervision can improve teacher performance in planning lessons at SDN Kawengen 01.